Pendampingan Usaha Mikro Kecil Menengah Untuk Meningkatkan Pengembangan Kapasitas Usaha Masyarakat Di Kelurahan Wringinanom - Mu'izz, Muhammad Abdul; Mariana, Mariana (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The mentoring program in this community partner is micro, small and medium enterprises (MSMEs) for catfish farming in kertosari Babadan Ponorogo Village. The problem they face are related to aspects of catfish farming, which are related to land managemen, business entities, and capital. Thish mentoring program is shown to empower and strengthen the community through MSMEs (Micro, Small and Medium Enterprises). The method used to overcome these problem is education to the community through training, cultivation and mentoring aimed at forming actors is the business sector, as well as managing the development of the business being run. With business empowermen carried out through the formantion of an institutional group AL-FIRDAUS this group thas 6 people in its group, and this line of business is used as a provision for the emergence of new entrepreneurs in the fisheries sector in overcoming the problem fased.